Management of Degenerative Spondylolisthesis: Analysis of a Questionnaire Study, Correlation With a National Sample, and Perioperative Outcomes of Treatment Options - BOVONRATWET, PATAWUT (Int J Spine Surg, 2019)
BACKGROUND: Surgical treatment for lumbar degenerative spondylolisthesis has been shown to provide better long-term outcomes than conservative treatment. However, there is variation in surgical approaches employed by surgeons. This study investigates current surgical practice patterns and compares perioperative outcomes of 3 common surgical treatments for this pathology. METHODS: A survey was administered to surgeons who attended the Lumbar Spine Research Society (LSRS) meeting in 2014. Data were extracted from the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) from 2005 to 2014 to characterize the same responses. The 2 data sets were compared. Perioperative outcomes of those in the ACS-NSQIP posterior fusion subcohorts were characterized and compared. RESULTS: Posterior surgical approaches utilized by surgeons who responded to the LSRS survey were similar to those captured by ACS-NSQIP where 72% of those with degenerative spondylolisthesis were fused. Of those that were fused, 8% had an uninstrumented posterior fusion, 33% had an instrumented posterior fusion, and 59% had an instrumented posterior fusion with interbody. On multivariate analysis, there was no difference in risk of postoperative adverse events, readmission, or length of stay between these 3 common types of fusion. CONCLUSIONS: Practice patterns for the posterior management of lumbar degenerative spondylolisthesis were similar between LSRS survey responses and ACS-NSQIP data. The ACS-NSQIP perioperative outcome measures assessed were similar regardless of surgical technique. These findings highlight that cost-benefit considerations and longer-term outcomes have to be the measures by which surgical technique is chosen for degenerative spondylolisthesis.